2022
DOI: 10.1111/nmo.14349
|View full text |Cite
|
Sign up to set email alerts
|

Overlap of heartburn, functional dyspepsia, and irritable bowel syndrome in a population sample: Prevalence, temporal stability, and associated comorbidities

Abstract: Background: Co-occurring (overlapping) irritable bowel syndrome (IBS), functional dyspepsia (FD), and heartburn has been observed. However, whether it is a distinct entity has not been established, nor what clinical, demographic, lifestyle, and psychological traits are associated with it. This study sought to estimate the prevalence and temporal stability of this overlap and to identify features specific to it in order to gain some insights into the potential etiopathogenesis.Methods: Two waves of a survey to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Jones et al . found that 2% of an Australian random community sample met the criteria for overlap GERD-FD-IBS, which was estimated to be twenty-fold greater than the expected probability by random chance [ 24 ]. Although the prevalences of OS in Asian countries are generally lower than in Western countries, these findings confirm that OS in the general population is common and does not occur by chance.…”
Section: Discussionmentioning
confidence: 99%
“…Jones et al . found that 2% of an Australian random community sample met the criteria for overlap GERD-FD-IBS, which was estimated to be twenty-fold greater than the expected probability by random chance [ 24 ]. Although the prevalences of OS in Asian countries are generally lower than in Western countries, these findings confirm that OS in the general population is common and does not occur by chance.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an Australian study showed no relationship between gender and overlap[ 25 , 28 ]. There seems to be a distinct overlap between IBS, FD, and gastroesophageal reflux disease (GERD), in which it is easier to merge psychological morbidity and sleep disturbance[ 29 ]. Although age, gender, and IBS subtype were not correlated with overlap[ 25 ], the pathogenesis analysis of IBS and FD indicates that psychological factors are linked to the overlap of IBS and FD.…”
Section: New Insights Into the Overlap Of Ibsmentioning
confidence: 99%
“…Further, FD patients can also exhibit certain overlaps with GERD and IBS, and are, therefore, often misclassified ( Quigley and Lacy, 2013 ; Pleyer et al, 2014 ; von Wulffen et al, 2019 ). Compared to patients with single FGID, those with overlap syndrome visit the hospital more frequently and report more frequent and severe gastrointestinal symptoms, more severe depression, as well as lower QOL ( Lee et al, 2020 ; Barberio et al, 2022 ; Jones et al, 2022 ). FGID overlap syndrome is often explained by diseases sharing the same pathophysiology (such as visceral hypersensitivity and gastrointestinal motility disorder) occurring in multiple organs instead of being confined to one gastrointestinal segment.…”
Section: Future Perspectivesmentioning
confidence: 99%